35.7k views
1 vote
Item 5 Solve for b. − 1 3 b=9 What is the answer?

User Timmi
by
5.3k points

2 Answers

4 votes

Answer:

For
b=(9)/(-13) so that
-13 * b=9 .

Explanation:

Given expression

- 13 b = 9

Here, -13 is multiplied with b on solving it gives 9 as answer.

We have to find b so that when it is multiplied with -13 it gives answer as 9.


-13 * b=9

When -13 is taken to other side operation gets inverse (multiplication changes to division) and -13 goes other side in denominator as,


\Rightarrow b=(9)/(-13)

Thus, for
b=(9)/(-13) so that
-13 * b=9 .

User Keen Jin
by
5.3k points
1 vote

Answer:

b = -27

Explanation:

-1/3 b = 9

Multiply each side by -3

-3 * -1/3 b = -3 * 9

b = -27

User Ehab
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.